Criteria for the Existence of Internal Fixed Points of Lotka-Volterra Quadratic Stochastic Mappings with Homogeneous Tournaments Acting in an $(m-1)$ - Dimensional Simplex - Eshmamatova, D.B.; Tadhzieva, M.A.; Ganikhodhzaev, R.N. (Journal of Applied Nonlinear Dynamics, 2026)
It is known, there is a close connection between discrete Lotka-Volterra systems and tournaments. In the paper, we give the concept of a homogeneous tournament, which allows us to obtain new results on the location of fixed points of the Lotka-Volterra systems on the simplex.